The Effect of Sensory - motor Perception Exercises on Learning Throwing and receiving Rings During Cat leap performance in Rhythmic gymnastics - Lalz, Kholod; Hassanein, Suaad (Journal of Physical Education, 2016)
Rhythmic gymnastics skills are considered closed skills thus they requireexercises that develop the students' perception of time and place. The aim of the research ispreparing special exercises for sensory – motor perception in learning throwing andreceiving skills in cat leap performance. In addition to that, the researcher aimed atidentifying the effect of these exercises on learning throwing and receiving rings in rhythmicgymnastics. The researchers used the experimental method on third year female students ofphysical education and sport Scinces College. The subjects were (12) students. The resultsshowed great variance in posttests between controlling and experimental group in favor ofthe experimental group.